Peptide-based drug discovery: Current status and recent advances - Sharma, Komal; Sharma, Krishna K.; Sharma, Anku; Jain, Rahul (Drug discovery today, 2023)
[Display omitted] •A comprehensive compilation and analysis of FDA approved and under clinical trials peptide-based therapeutics.•Clinical trial peptides pipeline analysis reveals emerging areas and drug targets.•Recent advancements in the synthesis and diversification of peptides using unnatural amino acids, late-stage and CH functionalization, and ligation techniques.•New advancements in peptide discovery through emphasis on emerging technologies such as DNA-encoded library and display techniques. The progressive development of peptides from reaction vessels to life-saving drugs via rigorous preclinical and clinical assessments is fascinating. Peptide therapeutics have gained momentum with the evolution of techniques in peptide chemistry, such as microwave irradiation in solid- and solution-phase synthesis, ligation chemistry, recombinant synthesis, and amalgamation with synthetic tools, including metal catalysis. Diverse emerging technologies, such as DNA-encoded libraries (DELs) and display techniques, are changing the status quo in the discovery of peptide therapeutics. In this review, we analyzed US Food and Drug Administration (FDA)-approved peptide drugs and those in clinical trials, highlighting recent advances in peptide-based drug discovery.